Early Localization of the Third Segment of the Vertebral Artery: The Atlanto-Mastoid Line. Issue 4 (December 2016) - Meybodi, Ali Tayebi; Rincon-Torroella, Jordina; El-Sayed, Ivan H.; Lawton, Michael T.; Benet, Arnau
Abstract : BACKGROUND: The third segment of the vertebral artery (V3) is vulnerable to injury during surgical approaches to the posterolateral craniovertebral junction. Despite numerous efforts, a roadmap to localize this segment of the artery is still lacking. OBJECTIVE: To delineate the topographic anatomy of the V3 and to facilitate a safe and fast exposure during transcranial surgical approaches to the posterior craniovertebral junction. METHODS: The distances between the most posteriorly prominent point (bulge) of the vertebral artery and the surrounding bony and muscular landmarks were measured in 10 cadaveric heads bilaterally (20 sides). The relative position of the vertebral artery bulge projected on the atlanto-mastoid line was calculated using trigonometric equations. Two clinical vignettes were reported to provide examples of clinical application of the described technique. RESULTS: The vertebral artery bulge was found within 10.8 mm of the atlanto-mastoid line. The projected position of the vertebral artery bulge on the atlanto-mastoid line lay within 40th and 50th percentiles of its length measured from the mastoid process in 16 (89%) specimens. The close relationship between the V3 segment and superior oblique capitis muscle makes this muscle another useful guide for localization of the V3 segment. CONCLUSION: The atlanto-mastoid line is a reliable guide for fast and safe exposure of the vertebral artery in the suboccipital triangle. Using this clue together with the belly of the superior oblique capitis muscle can lead the surgeon to the V3 segment safely, as illustrated in the clinical vignettes. ABBREVIATIONS: AICA, anterior inferior cerebellar artery AM, atlanto-mastoid OA, occipital artery SO, superior oblique SOT, suboccipital triangle V3, third segment of the vertebral artery VA, vertebral artery Abstract : Supplemental Digital Content is Available in the Text.